The shadow list - Moss, Todd (A Judd Ryker novel, 2017)
"A cutting-edge novel of international crime and its consequences, from Nigeria to Russia to Washington, from the former deputy assistant secretary of state. We laugh when it pops up in our inbox: the scam letter promising a windfall. We wonder: How does anybody fall for these things? But it is no laughing matter. It is one of the biggest organized crime rackets in the world, it is deadly - and State Department crisis manager Judd Ryker has fallen right into the middle of it. The disappearance of a young American in London sends Ryker into the heart of a corruption scandal in Nigeria, at the same time his CIA agent wife Jessica finds herself chasing a Russian master criminal known as the Bear. Unknown to either of them, they are pulling at two ends of the same lethal thread, a staggeringly vicious enterprise of piracy, extortion, and murder. The world is messy and dangerous, Jessica warns her husband. More dangerous than you know. But he is about to find out"--